Case Report: Clinical manifestations and treatment of two Chinese patients with FINCA syndrome carrying a novel variant of NHLRC2 - Yuemei Liu; Hongling Wang; Yu Tang; Lei Zhang; Yanyan Su; Yanqion Wang; Shasha Xu; Shiyue Mei; Chunyang Jia; Yuelin Shen; Xiaolei Tang (Frontiers in Pediatrics, 2024)
Fibrosis, neurodegeneration, and cerebral angiomatosis (FINCA) syndrome is an autosomal recessive genetic disorder caused by mutations in NHL-repeat-containing protein 2 (NHLRC2) gene. This case report describes two Chinese siblings with FINCA syndrome carrying a novel frameshift variant, c.1610dupT (p.L537Ffs*17), of NHLRC2 gene. They shared similar symptoms of interstitial lung disease (ILD) and neurodegeneration, with early onset during infancy, and shared similar chest CT findings of bilateral ground-glass opacities and consolidations. The elder brother died of infantile respiratory failure, while the younger brother showed improvement in respiratory symptoms, chest CT, and Krebs von den Lungen-6 levels after long-term systemic glucocorticoid therapy, indicating that anti-inflammatory treatment may be beneficial in the treatment of ILD caused by FINCA syndrome.